Dna damage in lymphocytes in chronic viral hepatitis B, C - A. O. Mikhailov; A. F. Popov; N. S. Ivanova; A. I. Simakova (Журнал инфектологии, 2017)
Objective: determine grade of DNA damage in lymphocytes and the levels of 8-hydroxy-2-deoxyguanosine (8- OHdG) and 8-nitroguanine (8-NO2G), total antioxidant activity (TAA) in the blood serum of patients with chronic viral hepatitis C (HCV), B (HBV).Materials and methods. The study included 100 people with HCV, 50 with HBV and 43 volunteers. DNA damage was evaluated by comet assay. Level 8-NO2G and 8-OHdG were determined in serum samples using ELISA kits. TAA determined according to the standard ABTS method. All statisticalcalculations were performed and the graphs were plotted using STATISTICA 10.0 software.Results. There was a tendency to increase the level of DNA damage with progression of the liver fibrosis stage in HCV and HBV. Significant differences from the norm of 8-NO2G in the F1, F2, F3 groups with HCV and in the groups F2, F3, F4 (ρ <0,05) with HBV were found. In the groups with HCV and in F2 and F4 with HBV, the level of 8-OHdG is higher in comparison with the control group (ρ = 0,0001). Correlations are shown between the stage of hepatic fibrosis and the level of 8-NO2G and 8-OHdG, respectively (r = 0,786620 and r = 0,625844; ρ <0,05) with CVHC and CVHB (r = 0,573933 and r = 0, 478849; ρ <0,05). In the study of OAA, the tendency towards its depletion with the development of fibrotic changes was noted in patients, however, significant differences in comparison with the control were only at the stage of F3 and F4 fibrosis in CVHC, and F2, F4 (ρ <0,05) with CHBV.Conclusion. Revealed the genotoxic effect of hepatitis B and C on the DNA of lymphocytes. An increasing degree of DNA fragmentation with the progression of liver fibrosis. The correlation between fibrosis and biochemical markers of DNA damage and decrease shown decompensated TAA serum in advanced stages of liver fibrosis.